Precision in Motion: The Dosimetric Edge of Adaptive Radiotherapy for Non-Small Cell Lung Cancer (NSCLC) - Thakur, Vandana; Sharma, Hardik; Prashar, Pratibha; Vias, Poorva; Chand, Bhagat; Thakur, Anupam (Asian Pacific Journal of Cancer Care, 2026)
Introduction: To evaluate the dosimetric advantages of adaptive radiotherapy (ART) in patients with inoperable Stage II–III non-small cell lung cancer (NSCLC), focusing on changes in target volumes and sparing of organs at risk (OARs) after mid-treatment re-planning. Settings and Design: This prospective, single-institution dosimetric study included patients treated with intensity-modulated radiotherapy (IMRT) between December 2023 and January 2025. Materials and Methods: Twenty-five patients with histologically confirmed NSCLC unsuitable for surgery underwent initial and mid-treatment planning using 4D-CT. IMRT plans were generated using Monaco® TPS, and re-planning was performed after 40 Gy based on updated tumor and OAR contours. Adaptive plans were implemented for treatment continuation. Paired t-tests evaluated changes in gross tumor volume (GTV) and planning target volume (PTV). Wilcoxon signed-rank tests assessed differences in dose–volume histogram (DVH) parameters between initial and adaptive plans. A p-value <0.05 was considered statistically significant. Results: Significant reductions in tumor volumes were observed post 40 Gy. Median primary GTV decreased by 40% (p = 0.001), nodal GTV by 52.3% (p = 0.001), and PTV by 36.2% (p = 0.001). ART led to substantial OAR sparing: ipsilateral lung V20 decreased by 49.6%, heart V5 by 45.5%, and mean esophageal dose by 24.5% (all p = 0.001). Conclusion: Adaptive radiotherapy offers significant dosimetric benefits in NSCLC by reducing radiation exposure to critical structures without compromising target coverage. These findings support broader clinical adoption of ART in medically inoperable NSCLC patients.